Particle Accretion Mechanism Underlies Biological Crystal Growth from an Amorphous Precursor Phase. (1st July 2014) - Gal, Assaf; Kahil, Keren; Vidavsky, Netta; DeVol, Ross T.; Gilbert, Pupa U. P. A.; Fratzl, Peter; Weiner, Steve; Addadi, Lia
<x xml:space="preserve">Abstract</x> Many biogenic minerals are composed of aggregated particles at the nanoscale. These minerals usually form through the transformation of amorphous precursors into single crystals inside a privileged space controlled by the organism. Here, in vitro experiments aimed at understanding the factors responsible for producing such single crystals with aggregated particle texture are presented. Crystallization is achieved by a two‐step reaction in which amorphous calcium carbonate (ACC) is first precipitated and then transformed into calcite in small volumes of water and in the presence of additives. The additives used are gel‐forming molecules, phosphate ions, and the organic extract from sea urchin embryonic spicules ‐ all are present in various biogenic crystals that grow via the transformation of ACC. Remarkably, this procedure yields faceted single‐crystals of calcite that maintain the nanoparticle texture. The crystals grow predominantly by the accretion of ACC nanoparticles, which subsequently crystallize. Gels and phosphate ions stabilize ACC via a different mechanism than sea urchin spicule macromolecules. It is concluded that the unique nanoparticle texture of biogenic minerals results from formation pathways that may differ from one another, but given the appropriate precursor and micro‐environment, share a common particle accretion mechanism.